Recent Advancements in the Cobalt Oxides, Manganese Oxides, and Their Composite As an Electrode Material for Supercapacitor: A Review - Uke, Santosh J.; Akhare, Vijay P.; Bambole, Devidas R.; Bodade, Anjali B.; Chaudhari, Gajanan N. (Frontiers in Materials, 2017)
In this smart edge, there is an intense demand of portable electronic devices such as mobile phones, laptops, smart watches etc. That demands the use of such components which has light weight, flexible, cheap and environmental friendly. So that needs an evolution in technology. Supercapacitors are energy storage devices emerging as one of the promising energy storage devices in the future energy technology. Electrode material is the important part of supercapacitor. There is much new advancement in types of electrode materials as for supercapacitor. In this review, we focused on the recent advancements in the cobalt oxides, manganese oxides and their composites as an electrodes material for supercapacitor.